Predicting undergraduate student outcomes: Competing or complementary roles of self-esteem, self-compassion, self-efficacy, and mindsets? - Wasylkiw, Louise; Hanson, Sophie; Lynch, Laurence MacRae; Vaillancourt, Elise; Wilson, Chelsea (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
Whereas several individual differences have been shown to predict academic and psychological outcomes among university students, it is not always clear which are most impactful, in part because many of the constructs overlap. Thus, the purpose of the present study was to examine the unique contributions of self-esteem, self-compassion, self-efficacy, and mindsets when predicting outcomes among university students. Undergraduate students (N = 214) completed an online survey including measures of the predictors as well as the outcomes of self-control, mental health, and both course and term grades. Correlations confirmed the overlap among the predictors highlighting the importance of examining the unique contributions of each. Results of multiple regression analyses showed that self-esteem and self-compassion explained unique variance in depression and anxiety over and above self-efficacy and growth mindsets. In contrast, self-efficacy and growth mindsets each significantly predicted self-control when controlling for self-esteem and self-compassion. Only self-efficacy predicted course grades. Given our results, we suggest that self-compassion and one’s beliefs about their abilities are complementary strengths for students attending university and should be considered when designing interventions to improve outcomes.